Smart Farming Using Mesh Network - Pankaj Singh Bora; Mohammad Sadique Ejaz; Syed Sibtain Khalid (International Journal of Wireless Security and Networks, 2024)
The increasing demand for food production due to the growth of the world population has led to various challenges in agriculture. Factors such as the reduction of the rural workforce and the rise in production costs have made it necessary to find innovative solutions to enhance productivity and efficiency. Smart farming, which integrates agricultural practices with the Internet of Things (IoT), has become a promising method to tackle these challenges. Smart farming leverages IoT technologies to enable the collection and analysis of data from various sources in the agricultural ecosystem. This approach, driven by data, enables farmers to make informed decisions and enhance their farming operations. The application of smart farming with IoT in agriculture has evolved over time. Initially, traditional approaches relied on reactive utilization of data, where farmers would respond to crop problems after they occurred. However, with recent technological advancements, the use of data in agriculture has shifted towards proactive and preventive approaches. Farmers can now leverage real-time data and predictive analytics to anticipate potential crop issues, optimize resource allocation, and enhance overall crop health and productivity.
Keywords: API; Cloud computing; Embedded system; Internet of things (IoT); smart farming